A Subclass of Harmonic Univalent Functions Associated with q-Analogue of Dziok-Srivastava Operator. (9th September 2013) - Aldweby, Huda; Darus, Maslina
Abstract : We study a class of complex-valued harmonic univalent functions using a generalized operator involving basic hypergeometric function. Precisely, we give a necessary and sufficient coefficient condition for functions in this class. Distortion bounds, extreme points, and neighborhood of such functions are also considered.